2017
DOI: 10.1111/pbi.12721
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic metabolic responses of brown planthoppers towards susceptible and resistant rice plants

Abstract: SummaryBrown planthopper (Nilaparvata lugens Stål, BPH) causes huge economic losses in rice‐growing regions, and new strategies for combating BPH are required. To understand how BPHs respond towards BPH‐resistant plants, we systematically analysed the metabolic differences between BPHs feeding on the resistant and susceptible plants using NMR and GC‐FID/MS. We also measured the expression of some related genes involving glycolysis and biosyntheses of trehalose, amino acids, chitin and fatty acids using real‐ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 57 publications
(73 reference statements)
2
52
0
Order By: Relevance
“…This is conceivable since Phe, Tyr, and Trp are precursors for biosynthesis of phenylpropanoids and tryptophan-related alkanoids which have antibacterial activity in plant resistance to biotic stressors (Abdel-Farid et al, 2009 ). Biosynthesis of osmolytes such as glucose, myo -inositol, betaine, and proline are important metabolic reprogramming strategy for plant resistance to both abiotic and biotic stressors (Choi et al, 2004 ; Browne and Brindle, 2007 ; Paranidharan et al, 2008 ; Bollina et al, 2010 ; Dai et al, 2010b ; Liu et al, 2010 , 2017 ; Zhang et al, 2011 ; Kumar et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is conceivable since Phe, Tyr, and Trp are precursors for biosynthesis of phenylpropanoids and tryptophan-related alkanoids which have antibacterial activity in plant resistance to biotic stressors (Abdel-Farid et al, 2009 ). Biosynthesis of osmolytes such as glucose, myo -inositol, betaine, and proline are important metabolic reprogramming strategy for plant resistance to both abiotic and biotic stressors (Choi et al, 2004 ; Browne and Brindle, 2007 ; Paranidharan et al, 2008 ; Bollina et al, 2010 ; Dai et al, 2010b ; Liu et al, 2010 , 2017 ; Zhang et al, 2011 ; Kumar et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabonomic analysis of wheat leaves and stem tissues indicated that the levels of betaine, sucrose, glucose, glutamate, glutamine, alanine, trans -aconitic acid and some aromatic compounds were positively correlated with FHB resistance (Browne and Brindle, 2007 ). Metabolomic phenotypes have also been reported for numerous plant-pathogen interactions including Brachypodium distachyon and Magnaporthe grisea (William Allwood et al, 2006 ), mulberry leaf and phytoplasma (Gai et al, 2014 ), BPH infestation of rice (Liu et al, 2010 , 2017 ), FG infected barley (Bollina et al, 2010 ), and wheat (Browne and Brindle, 2007 ; Paranidharan et al, 2008 ) together with chick pea (Kumar et al, 2016 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The TSP was used as a reference at δ 0.00. The metabolites were identified based on the 1 H-NMR spectra and comparisons with the NMR spectra of the reference compounds and published literatures (Fan 1996;Dai et al 2010;Kim et al 2010;Jones et al 2011;Nuringtyas et al 2012;Nam et al 2015;Uawisetwathana et al 2015;Liu et al 2017;Pramai et al 2017).…”
Section: H-nmr Analysismentioning
confidence: 99%
“…Resistant rice varieties have been reported to have significant effects on the overall BPH fitness, including feeding periods, survival, metamorphosis, and fecundity 20,21 . For instance, during the compatible rice-BPH interactions, probing and pathway (N 1 + N 2 + N 3 ) phases have been reported to be much shorter as compared to that of during the incompatible interactions 22 .…”
Section: Introductionmentioning
confidence: 99%